(untitled) (University Arena, 2025)
Background. Motivational dynamics is always manifested at the level of global behavior, which means that understanding the motivational orientation of behavior requires a systemic view of it. Objectives. Sports dance - whose specific means we used in the experimental study, are effective ways to develop the self-image, the motivational system and the motivation to achieve the self-image. 70 subjects participated in the research, students from different faculties within the University of Bucharest, based on registration in the sports dance class. Among them, 50 female students and 20 male students, aged between 19 and 25, first-year students at the University of Bucharest. All of them opted for the sports dance class at the beginning of the 2022-2023 academic year. Sports dance lessons were held throughout the academic year according to the curriculum. Methods. The observation method: were monitored the indicators related to the efficiency of the execution, the improvement of the posture, of the body attitude, the efficiency of the communication, the relationship with the others, as relevant elements for the studied phenomenon. In addition to direct observation, the video camera and the computer were used. Speaking: using dialogue to obtain useful information. For the present research, the preferred subjects are: knowledge of the particularities of the motivational system; hierarchical organization of motives; knowledge of the conditional determinative and inhibiting factors for practicing of sports dance; evaluation and knowledge of the relationship between achievement motivation and self-image. Questionnaire-based survey: the questionnaire was developed to study self-image and self-esteem. It was developed and applied in order to study the importance that the subjects give to the sports dance practiced in the physical education class for the development of the motivation to realize the self-image. Statistical-mathematical method – statistical-mathematical processing of the data resulting from the questionnaire. Graphical representation method: Microsoft Excel was used. Results. The obtained results were ranked according to the score, tabulated, interpreted and presented graphically. Conclusion. The processing of the subjects results from the initial and final testing, highlights the awareness that has occurred on the benefits that the practice of physical exercises, in general and sports dance, in particular, brings to personal development. From the results of the study, it emerged that Sports Dance develops social intelligence, interpersonal relationships, communication ability, emotional intelligence, the ability to make voluntary effort, perceptive qualities.